Green roofs, facades, and vegetative systems : safety aspects in the standards - Giacomello, Elena (Butterworth-Heinemann, and imprint of Elsevier, 2021)
Green Roofs, Facades, and Vegetative Systems: Safety Aspects in the Standards analyzes codes, standards and official documents from countries around the world, including: the United States and Canada in North America, Germany, France and Italy in Europe, and Australia, Singapore, Japan and Thailand in Asia. This essential resource for building design professionals covers a full range of living technologies, such as vegetative systems, green architecture/urban design, construction efficiency, facades, fire protection, sustainability aspects in buildings, landscape design, tall buildings and wind design. The book provides an invaluable tool on international codes and standards and how to incorporate them into projects.
Keywords: Green roofs (Gardening) -- Safety measures.; Green roofs (Gardening) -- Design and construction -- Standards.; Urban gardening -- Safety measures.; elektronické knihy; electronic books